2010
DOI: 10.1057/elmr.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the UK's human capital stock

Abstract: Estimates of the UK's stock of human capital are derived by applying a lifetime labour income methodology to data from the UK Labour Force Survey. The results show that using an annual discount rate of 3.5 per cent and assuming annual labour productivity growth of 2 per cent, the market value of the UK's human capital stock in 2009 was £16,686 billion. This is more than two-and-a-half times the Blue Book estimate of the Net Worth of the UK for the same year and £2,703 billion higher than the estimate for the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Although this study is somewhat controversial, Ebenstein [ 39 ] came to the same conclusion after improving the monitoring data: heavy pollution significantly increases the probability of heart and lung disease, thereby reducing life expectancy. Richard [ 40 ] found that in the UK, the human health level was affected by environmental quality, and the human health level was related to labor participation, which had a significant impact on economic output. Therefore, he concluded that environmental quality has an impact on economic output.…”
Section: Methodsmentioning
confidence: 99%
“…Although this study is somewhat controversial, Ebenstein [ 39 ] came to the same conclusion after improving the monitoring data: heavy pollution significantly increases the probability of heart and lung disease, thereby reducing life expectancy. Richard [ 40 ] found that in the UK, the human health level was affected by environmental quality, and the human health level was related to labor participation, which had a significant impact on economic output. Therefore, he concluded that environmental quality has an impact on economic output.…”
Section: Methodsmentioning
confidence: 99%
“…Human capital is defined as the ability attached to the workforce, which can further generate economic value and increase productivity. However, 'ability' as an abstract concept is difficult to quantify concretely, so the measurement of human capital has evolved into various forms in both theoretical and empirical studies, such as the degree of education [24], entrepreneurship [25], individual and collective human capital [26]. Apart from these studies, there is another strand of literature that focuses on the role of occupational groups in economic development (e.g., [2,25,[27][28][29]), exploring a 'joint force' of innovative ability of different occupations to regional and urban development.…”
Section: Historical and Theoretical Backgroundmentioning
confidence: 99%
“…However, it is one that some governments and sub-national entities have begun, with pioneering methodologies. The U.K.'s Office of National Statistics released an experimental estimate of its human capital stock, including a detailed methodology for valuing the productive capacity of citizens (Jones and Chiripanhura, 2010). The United Nations' System of Integrated Environmental and Economic Accounts (SEEA) (United Nations, 2014) has been revised to include a framework for valuing the market and non-market goods and services provided by natural capital.…”
Section: An Oregon Shareholder's Reportmentioning
confidence: 99%